Expanding the concept of transnational cinema through branded content in the digital age - Lee, Kyung Hee; Kim, Kenneth Chi Ho; Kim, Yong Bae (Frontiers in Communication, 2026)
This perspective article offers a conceptual and exploratory framework for understanding how branded content expands the conceptual boundaries of transnational cinema in the digital age. Rather than offering empirical generalizations, it encourages theoretical discussions and future research. While previous studies focused on auteurism and art films, this article argues that branded content shaped by hybridity, technology, and layered narratives can be a distinct cinematic form that crosses borders. Moving beyond Jenkins’s triad of immersion, convergence, and extension, this article proposes an affective, technological, and interpretive lens to reframe the global circulation of branded narratives. Hyundai Motor Company’s short film Night Fishing (2024) was used as a conceptual illustration that demonstrates how branded content engages transnational audiences through emotional immersion, narrative hybridity, and dual distribution across theatrical and digital platforms. Ultimately, this article suggests that branded content bridges commercial intentions and artistic experiences, thus offering new grounds for conceptualizing transnational cinema in the digital era.